People’s Politics: The Way for Thai politics - Nimpanich, Jumpol; Suksamran, Somboon; Unkulwongwattana, Unkharintn; Wannapak, Surawong; Pong-isawaranan, Nanthaporn (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this research were (1) to study the development of civil politics from the Black May 1992 until the end of the Constitution in 1997 and 2007. (2) to study the civil politics in terms of the way for Thai politics, and (3) to study the problems and obstacles of the civil politics as an alternative or the way for Thai politics. The research design used mixed methods, both qualitative research and quantitative research. The sample size was 400 selected by random sampling from the population in Nonthaburi, Nakhon Pathom, Pathumthani, Samutprakarn, and SamutSakhon provinces. Data were analyzed by frequency, percentage, mean, standard deviation, standard regression coefficient (b), and multiple correlation coefficient (R). There was a relationship between variables by multiple regression analysis, Cronbach’s Coefficient of alpha and descriptive analysis. The results showed that:First The results of data analysis from the first objective: civil politics since the aftermath of May in 1992, until the end of the Constitution in 1997 and 2007, found that the development of civil politics has been in a progressive direction. Second, the characteristics of civil politics from 7 case studies found that the nature of civil politics, both rural and urban movements, were systematic direction, whether considering as structural, process and behavioral to change or to create a new set of rules for their goals and Third, the problems and obstacles of the rural and urban movement were: the political and public sector ignored to comply with the Constitution in 1997 and 2007; according to the researchers’ perspectives, the conflict had been occupied. It was creative and destructive as dynamics, therefore, to reduce or eliminate political conflict by using the dialogue to find a way to resolve the conflict by peaceful means without political violence. Therefore, the use of peaceful means between both sides by having increased their knowledge, understanding, and willingness to accept would be an alternative way out of Thai politics.